Training on English Material Making Using CarouselMaker for Students in the English Education Study Program - Zebua, Meniati; Zebua, Agustin Ceria; Lature, Hendrikus Agusman; Telaumbanua, Yasminar Amaerita (Perkumpulan Kualitama Edukatika Indonesia, 2025)
This study explores the effectiveness of training in developing English language teaching materials using the CarouselMaker platform among fourth-semester English Education students at Nias University. The program aimed to equip students with skills in creating interactive and digital-based learning content suitable for 21st-century classrooms. A descriptive qualitative method was employed, with data collected through questionnaires, and field notes. Results indicate that while most participants improved their technical ability in using CarouselMaker, many still relied on facilitator guidance and lacked confidence in applying the tool independently. Discussion participation was also limited. Despite these challenges, students showed enthusiasm for continuing similar trainings and recognized the relevance of digital tools in modern English Language Teaching (ELT). The findings highlight the need for extended mentoring and a personalized training approach to strengthen participants’ independence and pedagogical confidence. This training underscores the importance of preparing future English teachers to utilize digital media effectively, fostering innovation and engagement in the learning process.